Pituitary Apoplexy and Subdural Hematoma after Caesarean Section - Van Trung Hoang; The Huan Hoang; Thanh Tam Thi Nguyen; Vichit Chansomphou; Duc Thanh Hoang (Hindawi Limited, 2022)
Pituitary apoplexy can occur postpartum, and subdural hematoma following epidural anesthesia is a rare complication. Cooccurrence of these two complications is extremely rare and has not been previously reported in the literature. In this article, we present a case of pituitary apoplexy along with intracranial subdural hematoma happening two days after spinal anesthesia for cesarean section. The patient presented with peripheral facial nerve paralysis accompanied by headache, eye pain, and blurred vision and was diagnosed by imaging modalities. The patient made a good recovery with conservative treatment without serious health events.